2002
DOI: 10.1093/brain/awf140
|View full text |Cite
|
Sign up to set email alerts
|

Cortical excitability changes induced by deafferentation of the contralateral hemisphere

Abstract: Short-term deprivation of sensory input by ischaemic nerve block (INB) leads to functional reorganization in the deafferented motor cortex. Here, we show that INB also elicits functional changes in homotopic regions of the cortex contralateral to the deafferented one. We measured motor evoked potential (MEP) amplitudes elicited by transcranial magnetic stimulation (TMS) in small hand and biceps brachii muscles before, during and after INB of the right hand. INB increased excitability of the cortical representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
125
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 68 publications
(78 reference statements)
13
125
0
Order By: Relevance
“…Increases in cortical excitability were also shown to be accompanied by increases in AMPA receptor autoradiographic binding (53) and decreases in GABA staining in the deprived S1 (53,54). Moreover, increases in motor-evoked potential in the motor cortical representations contralateral and ipsilateral to the nerve injury in human subjects were blocked after administration of GABA agonists (24).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Increases in cortical excitability were also shown to be accompanied by increases in AMPA receptor autoradiographic binding (53) and decreases in GABA staining in the deprived S1 (53,54). Moreover, increases in motor-evoked potential in the motor cortical representations contralateral and ipsilateral to the nerve injury in human subjects were blocked after administration of GABA agonists (24).…”
Section: Discussionmentioning
confidence: 92%
“…Additional evidence indicates that the increase of inhibitory neuronal activity in the deprived cortex may be the foundation of the poor recovery and pain observed in patients suffering from nerve injury (24,25,57). Moreover, previous studies suggested that these evoked increases in inhibitory activity are mediated through the transcallosal pathway (20,21).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, an acute upper limb deafferentation induced a focal increase in the excitability of the non-deafferented hand motor cortex (Werhahn et al, 2002a;Floel et al, 2008) together with improvements in the non-deafferented hand in either tactile spatial acuity in healthy subjects (Werhahn et al, 2002b) and in hand motor performance in patients with stroke (Floel et al, 2008).…”
Section: Immobilization Effectmentioning
confidence: 99%
“…This occurs in healthy adults (20) and in stroke patients when the intact hand is anesthetized (21) and argues against activating the non-paretic arm and hand while training the paretic arm and hand. Furthermore, there is evidence that some patients with chronic stroke and larger impairments have an abnormally high interhemispheric inhibitory drive from M1 in the contralesional hemisphere to M1 in the ipsilesional hemisphere (22).…”
Section: Introductionmentioning
confidence: 99%